Vincent Gayon, L’OCDE au travail. Contribution à une sociologie historique de la « coopération économique internationale » sur le chômage et l’emploi (1970-2010) - Vincent Gayon (Revue de la Régulation)
If the OECD’s publications are often referred to or criticized, very few academic efforts have actually tried to analyze their elaboration. Based on the organization’s archives, the objective of this thesis is to fill in this gap by analyzing the production of OECD expertise on unemployment and employment, from the beginning of the 1970s to nowadays. The OECD is an institution marked by political and scientific power struggle, and influenced by political evolutions in its key member countries. Through this expertise, it is more largely the evolution of economic policy models that is questioned in an international framework: the assertion of a « monetarist consensus » overtaking the post-war « Keynesian consensus » in the 1970-1980s, and the promotion of « active » social policies in the 1990-2000s. This transformation of economic policies redefines the role of the state in the economic system, the political nature of unemployment and solutions that can be brought to this issue, and the forms of international economic cooperation itself (through benchmarking). The OECD is directly related to the transformations it tries to anticipate,provoke or rationalize.